Palmar and plantar pits related to Gorlin syndrome. - Cutrone, M. (European Journal of Pediatric Dermatology, 2007)
Palmar and plantar pits can be due to trivial causes such as bacterial infections due to Micrococcus sedentarius or other bacteria and favored by heavy and closed shoes and by poor hygiene. However, physician should be aware that plantar pits are a typical sign of Gorlin syndrome.